2014
DOI: 10.1016/j.livsci.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Daily and alternate day supplementation of Moringa oleifera leaf meal or soyabean meal to lambs receiving oat hay

Abstract: We hypothesized that Moringa oleifera foliage which is high in crude protein and almost free in main secondary compounds could replace soyabean meal used in supplementation strategies of livestock. Therefore, this experiment aimed to evaluate the effect of daily and alternate day supplementation of Moringa leaf meal (MLM) or soybean meal (SBM) to sheep on intake and digestion and glucose, protein and urea in blood plasma. Twenty Barbarine male lambs (average initial body weight, 27.373.0 kg), were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…Notably, we also observed a significant decrease in rumen urea nitrogen in calves fed an MLM-supplemented diet. These results are consistent with those observed in previous studies ( Jelali and Salem, 2014 , Kholif et al, 2015 , Kholif et al, 2018 ). There are several possible explanations for this result.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Notably, we also observed a significant decrease in rumen urea nitrogen in calves fed an MLM-supplemented diet. These results are consistent with those observed in previous studies ( Jelali and Salem, 2014 , Kholif et al, 2015 , Kholif et al, 2018 ). There are several possible explanations for this result.…”
Section: Discussionsupporting
confidence: 94%
“…Dietary inclusion of M. oleifera significantly decreased the concentrations of serum triglycerides and cholesterol but increased (p < 0.05) the concertation of serum glucose in lactating goats ( Kholif et al, 2016 ) and lactating dairy cows ( Zeng et al, 2018 ). In contrast, Jelali et al (2014) illustrated that MLM diet decreased (p < 0.05) serum total proteins and urea concentrations but had no impact on serum glucose concentration (p > 0.05).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The corresponding values of relative percentage of net revenue were 100, 56.45, 171.83 and 125.6 %. These results were in harmony with those of Jelali et al (2014) who found that using moringa leaves in growing lambs decreased feed cost and increased the economic return. Also, Mahmoud (2013) found that the concentrate feed mixture could be replaced by moringa while improved animal performance and increased net return.…”
Section: Economical Evaluation and Conclusionsupporting
confidence: 88%
“…Moreover, there is demand for over 500 million tons of grain to supply the agricultural sector (FAO, 2012) because of the increasing demand for animal products by the general population. Soybean meal is the main protein ingredient used around the world in animal diets (Jelali & Ben Salem, 2014). However, soybean meal is an expensive commodity that increases the cost of animal production.…”
Section: Introductionmentioning
confidence: 99%